2002
DOI: 10.1080/096293502900000113
|View full text |Cite
|
Sign up to set email alerts
|

Interference of a short‐term exposure to nitrogen dioxide with allergic airways responses to allergenic challenges in BALB/c mice

Abstract: Nitrogen dioxide (NO(2)) is a common indoor and outdoor air pollutant whose role in the induction of asthma is unclear. We investigated the effects of NO(2) on the development of asthma-like responses to allergenic challenge in BALB/c mice. Ovalbumin (OVA)-immunized mice were intranasally challenged with OVA or saline solution just before starting a 3 h exposure to 5 or 20 ppm NO(2) or air. Twenty parts per million of NO(2) induced a significant increase of bronchopulmonary hyperreactivity in OVA-challenged mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…Although the dose of NO 2 administered to our mice was higher than those used in a number of previous studies (16,22,23,40) and are higher than the concentrations seen in ambient air, the actual concentrations of NO 2 that reach the lung tissue are likely to be far lower than 25 ppm, given the high reactivity of NO 2 toward airway surface lining components. Consequently, the patterns of tyrosine nitration observed within the lung tissue in situ using the current NO 2 exposure regimen were not substantially different from air controls (data not shown).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Although the dose of NO 2 administered to our mice was higher than those used in a number of previous studies (16,22,23,40) and are higher than the concentrations seen in ambient air, the actual concentrations of NO 2 that reach the lung tissue are likely to be far lower than 25 ppm, given the high reactivity of NO 2 toward airway surface lining components. Consequently, the patterns of tyrosine nitration observed within the lung tissue in situ using the current NO 2 exposure regimen were not substantially different from air controls (data not shown).…”
Section: Discussionmentioning
confidence: 64%
“…These discrepancies can be explained by differences in the time frame of exposure to NO 2 relative to the OVA challenge, the concentration and/or the duration of NO 2 inhalation, and the genetic backgrounds of mice investigated. For example, using allergen-sensitized BALB/c mice exposed to 20 ppm NO 2 immediately before an intranasal challenge with allergen, Proust et al (40) reported enhanced AHR and lung permeability 24 h after exposure, despite a lack of alterations in eosinophil numbers in the BALF at 24 or 72 h after challenge and a reduction of late mucosal metaplasia compared with mice sensitized and challenged with allergen (OVA) alone. This group also reported that 5 ppm NO 2 caused a reduction in many of the measured features of allergic airway disease (40).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The production of MMP-12 was stimulated by IL-1b and TNF-a, and was found to promote cell migration (Xie et al 2005). In addition, deficiency in MMP-9 in a mouse model was found to be associated with decreased lung or alveolar injury (Lanone et al 2002;Proust et al 2002;Zuo et al 2002). Further, increased MMP-2 and -14 activity was found to be associated with asthmatic airway smooth muscle (Henderson et al 2007).…”
Section: Introductionmentioning
confidence: 94%